Sino-U.S. rebalance in South China Sea : a Chinese perspecitve - Shi, Xiaoran (2017)
This paper will discuss the influence of U.S.'s "Rebalance to Asia Pacific" strategy on South China Sea (SCS) issues and Sino-U.S. relations. The focus will be put on three questions, which are the reason that disputes rose again in SCS since 2009, China's reaction, and influence of U.S's rebalance on SCS issues and Sino-U.S. relations. With a perspective of balance of power theory, this paper will argue three points. First, U.S.'s rebalance is both a posture itself and an implicit support to the weaker side of the participants. Second, China's response was consistently strong on territorial disputes. Economic benefit and security demand, China's growing capability and tensions intensified by U.S.'s rebalance all contribute to China's stronger posture than before, didn't change China's caution on dealing with these issues. Third, SCS issues show no clue to get rid of control, since it's only a part of Sino-U.S. relations.